Mini-Review: Omental Patch Repair of Giant Perforated Peptic Ulcer - Syaiful, Ridho A; Agustian, Muhammad F (The New Ropanasuri Journal of Surgery, 2022)
Introduction. A perforated giant peptic ulcer is an emergency that requires surgery. Closure of the perforation with an omental patch has been reported in several cases of perforated giant peptic ulcers. However, there is insufficient evidence regarding the option of preferred treatment. This review to discuss published reports of a perforated giant peptic ulcer closed with an omental patch that focused on the complications Method. The literature search was conducted through the Cochrane, PubMed, Scopus, and EBSCO data sites. The articles obtained were screened for duplication, title, abstracts, and full-text based on inclusion and exclusion criteria. Result: Two articles were included in this study for critical review. From these two articles, no complications were reported regarding the closure of giant perforated gastric ulcers with an omental patch. Conclusion: In general, closure of perforated gastric has a minimal incidence of postoperative complications. An omental patch can be used to close gastric perforation in unusual cases, such as giant perforation and septic shock, as presented in this case.